KAJIAN MATERIAL DRIVEN DESIGN DALAM DESAIN AKSESORIS FASHION BERBASIS EKSPLORASI MATERIAL SWAKRIYA - Martono, John; Puspita, Eka Arifianty (Serat Rupa: Journal of Design, 2022)
Fashion design has a prominent role in constructing people’s performance due to its capability of communicating user’s personality. However, prior studies reveal that fashion design is not only able to work as a medium of self-representation, but also as an agent to stimulate certain action to the user. In response to the statements, material selection of fashion design contributes significantly in building consumer appraisement towards products because the material is the dominant element in fashion product aesthetic. Consumers may have various personal experiences and perception regarding material in a fashion product. Following the statement, this research is trying to investigate the integration of material experience study in a fashion design process to reach a more successful outcome of fashion design. Thus, this research is adopting Karana (2015) method of Material Driven Design. By conducting MDD method in the design of fashion product, it was found that there were diverse material experiences amid the users. Furthermore, by utilizing do-it-yourself approach of material development in the fashion design process reveals the possibilities of transforming material experience and the emergence of a new quality for the users to experience, especially an interpretative experience. The research outcome suggests the implementation of material experience study in the fashion design process, like the MDD method. The integration of material studies may not guarantee achieving a perfect user satisfaction, but the material experience study will help designers in understanding the background of user perceptions and finding novelty in the creation fashion design.